Dynamic Behaviour of Railway Track - Experimental Measurements - Milan Moravcik (Communications - Scientific letters of the University of Zilina, 2002)
The objective of the paper is devoted to in situ dynamic measurements on the track structure under traffic and briefly to present some experimental approaches in order to appreciate the dynamic behaviour of the track structure. The vertical vibration of rails, sleepers and free ballast field at a distance of 1m from the track and the direct dynamic interaction force the rail / the sleeper were measured and analysed in the time and frequency domain. Received results can give many usefulindications concerning the assessing of the superstructure dynamic behaviour.